show that prob (AUB)=prob(A)+prob(B)-prob(AnB).in particular ,if A and B are independent events,then prob(AuB)=prob(A)+prob(B)-prob(A)*prob(B)  Consider a probability space S with probability...

show that prob (AUB)=prob(A)+prob(B)-prob(AnB).in particular ,if A and B are independent events,then prob(AuB)=prob(A)+prob(B)-prob(A)*prob(B)

 

Consider a probability space S with probability function prob. Let A, B is element of s be two events.

Asked on by maha12

3 Answers | Add Yours

lambert86's profile pic

lambert86 | Student, Undergraduate | (Level 2) eNoter

Posted on

If A and B are two events of the sample space;Let B' be complementry event of B, By drawin a venn diagran you can clearly see that,

(AnB')n(B) = null

Therefore (AnB') and B are mutually exclusive events.

So, P[(AnB')U(B)]= P(AnB')+P(B);

But, from venn diagram you can observe that;

(AnB')U(B)=(AUB)

Therefore;

P[AUB]= P(AnB')+P(B)............(1)

Let us consider AnB';

If A and B are two events of the sample space;Let B' be complementry event of B, By drawin a venn diagran you can clearly see that,

(AnB')n(AnB)={}=Null

Therefore, (AnB') and (AnB) are mutually exclusive events.

P[(AnB')U(AnB)]=P(AnB')+P(AnB)

But, from the venn diagram (AnB')U(AnB)=A

Therefore;

P(A)=P(AnB')+P(AnB)

P(AnB')=P(A)-P(AnB).........(2)

By substituting From (2) to (1);

P[AUB]= P(A)+P(B)-P(AnB)...........(i)


By the definition of conditional probability,

P(A\B)=P(AnB)/P(B)

Therefore P(AnB)=P(A\B)*P(B)........(3)

If A and B are independent events occurance of B doesn't affect the occurance of A.

Therefore;

P(A\B)=P(A)

Subsitituting to (3);

P(AnB)=P(A\B)*P(B)=P(A)*P(B)

By subsituting to (i);

P[AUB]= P(A)+P(B)-P(A)*(B)

Think you have knowledge on venn diagrams.



 

 

 

 

 

vishnuip's profile pic

vishnuip | Student, Undergraduate | (Level 1) Honors

Posted on

If event A occurs B will not occur then P(A)=1 , P(B)=0 then P(A)*P(B)=0 vice versa. 

vishnuip's profile pic

vishnuip | Student, Undergraduate | (Level 1) Honors

Posted on

If A and B are independant events then there will be no common elements. Hence A & B will not occur simultaneously so P(A)*P(B) will be zero . We know that P(AuB)=P(A)+P(B) if A and B are independant . Since P(A)*P(B)=0 we can write P(AuB)=P(A)+P(B)-P(A)*P(B) .

We’ve answered 318,929 questions. We can answer yours, too.

Ask a question